'Dark Cloud with a Silver Lining'? The Prospect of a Rise in Material Values or a Post-Material Turn in Post-Pandemic South Africa. Issue 1 (2nd January 2021) - Struwig, Jarè; Roberts, Benjamin J.; Gordon, Steven L.
Abstract: The quarter century following the historic 1994 elections in South Africa and the establishment of a democratic dispensation was a period of transformative change. During this time, nation-building efforts were undertaken as a means of promoting redress, overcoming the country's colonial, segregationist and apartheid past, and challenging traditions of racialised citizenship. Progressive legislation was adopted that challenged traditional apartheid-based norms and laid the foundation for a fairer society based on the principles of " ubuntu ", encouraging a sense of community-oriented reciprocity. However, the policy choices made by the post-apartheid state have not translated into economic opportunities for millions of South Africans. Poverty, unemployment and inequality persist as pressing societal concerns, which has fostered widespread disenchantment and forced many to depend on survivalist strategies. This has created barriers to the attainment of a more caring society. The COVID-19 pandemic has deeply affected South African society, with a hard national lockdown triggering untold suffering and what promises to be one of the worst economic recessions. This article uses historical and current data to draw inferences about the likely impact of COVID-19 on South Africa. It considers whether the country's post-pandemic society will be characterized by a rise in materialistic values or alternatively new demands for a more humane society.